Associations of recent weight loss with health care costs and utilization among older women. - John T Schousboe (PLoS ONE, 2018)
The association of weight loss with health care costs among older women is uncertain. Our study aim was to examine the association of objectively measured weight change with subsequent total health care (THC) costs and other health care utilization among older women. Our study population included 2,083 women (mean age 80.2 years) enrolled in the Study of Osteoporotic Fractures and U.S. Medicare Fee for Service. Weight loss and gain were defined, respectively, as ≥5% decrease and ≥5% increase in body weight, and weight maintenance as <5% change in body weight over a period of 4.5 years. THC costs, outpatient costs, hospitalizations, and skilled nursing facility [SNF] utilization were estimated from Medicare claims for 1 year after the period during which weight change was measured. The associations of weight change with THC and outpatient costs were estimated using generalized linear models with gamma variance and log link functions, and with hospitalizations and SNF utilization using logistic models. Adjusted for age and current body mass index (BMI), weight loss compared with weight maintenance was associated with a 35% increase in THC costs ($2148 [95% CI, 745 to 3552], 2014 U.S. dollars), a 15% increase in outpatient costs ($329 [95% C.I. -1 to 660]), and odds ratios of 1.42 (95% CI, 1.14 to 1.76) for ≥1 hospital stay and 1.45 (95% CI, 1.03 to 2.03) for ≥1 SNF stay. These associations did not vary by BMI category. After additional adjustment for multi-morbidity and functional status, associations of weight loss with all four outcomes were no longer significant. In conclusion, ≥5% weight loss among older women is not associated with increased THC and outpatient costs, hospitalization, and SNF utilization, irrespective of BMI category after accounting for multi-morbidity and impaired functional status that accompany weight loss.